Feasibility and Applicability of Solar Disinfection (SODIS) for Point-of-use Water Treatment in Bandar Abbas, South of Iran - Leila Rezaei (Journal of Global Pharma Technology, 2017)
Today, drinking water supplies for most of the developing countries which mainly includes the remote villages are at stake. Therefore, using of low-cost and available methods, for the treatment of surface water for drinking in the areas without safe water system or emergency conditions was approved by international healthcare organizations. Solar disinfection technology (SODIS), is one of the most important technologies. In this study, the effect of UV-A radiation of sunlight in surface water disinfection in Bandar Abbas was studied. In a cross-sectional study, the samples have been exposed to sunlight for 1 to 7 hours in two types of PET and glass containers. Using of HPC method was measured number of remaining bacteria in the samples. Then, by using a statistical analysis, the relationship between reduce of microbial load and turbidity, contact time, weather conditions and type of containers was investigated. The results showed that removal efficiency of bacteria increased by increasing contact time from 1h to 7h. Also there was a direct and inverse relationship respectively between environmental temperature and turbidity with disinfection efficiency. Also results showed that in glass containers was observed more microbial load reduction. Noticed to significant impact of turbidity on SODIS, it is recommended, a filtration step performed prior to disinfection to reduce water turbidity. Based on the findings, the use of SODIS as a simple and practicable method is recommended to guarantee the drinking water safety.Keywords: Solar disinfection, SODIS, poInt-of-use, Water treatment, Bandar Abbas.